Effects of Vitamin E on Redox balance in regulating thiol/disulfide homeostasis in sepsis: An antioxidant therapy perspective - Veli Fahri Pehlivan; Başak Pehlivan; Erdogan Duran; Abdullah Taskın; Ismail Koyuncu; Yusuf Çakmak (PLoS ONE, 2025)
Background Sepsis, a life-threatening condition resulting from a dysregulated host response to infection, is associated with high mortality and remains a major global health burden. Sepsis is characterized by an imbalance between oxidative stress and inflammation, leading to disruption of thiol–disulfide homeostasis, hematological abnormalities, cytokine dysregulation, and widespread tissue injury. Methods An experimental sepsis model was established in thirty-two male Balb-C mice using lipopolysaccharide administration. Animals were randomized into four groups: control, vitamin E, sepsis, and sepsis plus vitamin E. Serum oxidative stress markers, thiol-disulfide parameters, and inflammatory mediators, including C-reactive protein, interleukin-40, and tumor necrosis factor-alpha, were measured. Hematological indices of systemic inflammation were evaluated (Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio), and lung, liver, and kidney tissues were examined histologically using a semi-quantitative scoring system. Results Lipopolysaccharide-induced sepsis caused marked disruption of thiol-disulfide balance, characterized by reduced native and total thiol levels, elevated disulfide levels, increased cytokine release, and severe histopathological injury. Vitamin E supplementation restored thiol-disulfide homeostasis, decreased oxidative stress, and attenuated systemic inflammation. In the sepsis plus vitamin E group, serum thiol levels increased significantly, while disulfide levels declined. Interleukin-40 showed a 24.2% reduction and tumor necrosis factor-alpha a 9.8% reduction compared with untreated septic animals. Histopathological analyses confirmed reduced inflammatory cell infiltration, vascular congestion, and tissue degeneration, particularly in the lungs. Conclusions Vitamin E demonstrated significant protective effects against sepsis-induced oxidative and inflammatory injury by preserving thiol-disulfide homeostasis and reducing cytokine production. The more pronounced effect on interleukin-40 compared with tumor necrosis factor-alpha suggests selective modulation of inflammatory pathways and highlights interleukin-40 as a potential biomarker and therapeutic target. These findings support vitamin E as a promising adjunctive therapy in sepsis, although further studies are required to define optimal dosing strategies and assess clinical applicability.